Evaluation of an on-capillary copper complexation methodology for the investigation of in vitro metabolism of dynorphin A 1–17 - Kuhnline, Courtney D. (2010)
Dynorphin A 1–17 is an endogenous neuropeptide implicated in a variety of neurological disorders including Alzheimer’s and Parkinson’s diseases and neuropathic pain. Metabolites of this peptide can exhibit their own unique effects in vivo, and it is possible that one of these metabolites is responsible for the neurotoxicity. In this article, the use of CE for the separation of dynorphin A 1–17 from four of its metabolites is described. Buffer additives were investigated to eliminate peptide adsorption to the capillary wall and to improve resolution between closely related metabolites. On-capillary copper complexation was employed and was shown to improve separation efficiency as compared with the separation of native peptides. The method was then applied to in vitro dynorphin metabolism in human plasma as well as rat brain and rat spinal cord slices.